Need Analysis for Development of Web-Based Flipped Classroom Learning Models in Vocational Education. Issue 1 (February 2021) - Ambiyar,; Efendi, Raimon; Waskito,; Rojiyyah, Iffah; Wulandari, Ratih Agustin
Abstract: This study aims to determine the potential and needs of lecturers and students in studying computer network security which will be used as a basis for developing a web-based inverted classroom model in vocational education. This research is also based on 21st century learning competencies needed in the digital age such as critical thinking, communication, collaboration and creativity. This research needs analysis consists of field observations and literature studies. This research is a type of descriptive research. The results of this study indicate that lecturers and students need a learning environment that integrates technology in learning so as to enable students to communicate and get information from various sources. Based on the needs analysis conducted, learning innovation is needed in the form of developing web-based flipped classroom models that are expected to create learning competencies that are more effective, efficient, interesting, and able to improve learning competencies and learning abilities of 21st Century students.